The Out-of-sync Child Recognizing and Coping with Sensory Processing Disorder - Carol Stock Kranowitz (U.S.A Penguin Books Ltd., 2005)
The Out-of-Sync Child broke new ground by identifying Sensory Processing Disorder, a common but frequently misdiagnosed problem in which the central nervous system misinterprets messages from the senses. This newly revised edition features additional information from recent research on vision and hearing deficits, motor skill problems, nutrition and picky eaters, ADHA, autism, and other related disorders.
Keywords: Counselor -- Counselor